Abnormal Elevated CA 19-9 in the Dermoid Cyst: A Sign of the Ovarian Torsion?. (11th June 2013) - Artunc Ulkumen, Burcu; Goker, Asli; Pala, Halil Gursoy; Ordu, Sercin
Abstract : Dermoid cyst is the most common germ cell tumor of the ovary containing various tissue elements. Ovarian torsion is a common complication of which ultrasonographic diagnosis is confusing. We report here a 14-year-old adolescent with painless torsion of the ovary including dermoid cyst and with abnormal elevated CA 19-9 serum levels. Elevated CA 19-9 level may be related to ovarian torsion and may predict the extent of tissue necrosis.